COMMUNITY PARTICIPATION IN PHYSICAL TRANSFORMATION OF TOURISM KAMPUNG: THE CASE OF KAMPUNG LAWAS MASPATI - Perbawanti, Nooraini Dewayani; Pratiwi, Wiwik Dwi; Samsirina, Samsirina (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2025)
Urban kampungs in Indonesia are increasingly being transformed into tourism destinations as part of urban revitalization efforts. However, these transformations often focus on aesthetic improvements and economic outputs without adequately considering the role of community participation in shaping the physical environment. This study investigates how spatial transformation in Kampung Lawas Maspati, Surabaya, is driven not only by policy interventions but also by internal community agency and collaboration with external actors. Using a qualitative descriptive approach with a case study method, the research draws on in-depth interviews, field observation, and spatial mapping through GIS. The analysis focuses on three stages of participation: planning, implementation, and evaluation—and is structured around key transformation categories: public space reorganization, tourism infrastructure integration, and the expression of place identity. The findings reveal that initial transformation was driven by local leadership who mobilized community action toward kampung revitalization. These efforts laid the foundation for formal recognition as a tourism kampung in 2016. The community not only initiated environmental and spatial improvements but continued to co-develop infrastructure with institutional support, including CSR involvement. This changes—community-led in vision, institutionally supported in execution—demonstrates a sustainable form of transformation grounded in local agency. The study highlights how participatory action and place-based leadership are critical to the success and longevity of tourism kampung development. It offers a framework for understanding how physical transformation is shaped through evolving participation and collaboration from the community.